Incumbent repositioning with decision biases - Du, Xianjin; Li, Meng; Wu, Brian (Strategic Management Journal, 2019)
[Research Summary:Incumbent firms often reposition themselves in response to entrants, but when doing so they incur repositioning costs. Incumbent repositioning costs and the associated decision biases have been identified in the economics, operations, and strategy literatures as critical aspects of the competitive interactions between incumbents and entrants, but they have received limited attention in game-theoretic treatments at the strategy level. To fill this gap, we develop a strategic mental model to analytically characterize the impacts of repositioning costs and decision biases on firms' equilibrium strategies and profits. Including these costs and biases changes, the nature of strategic dynamics as well as introduces new implications for strategic choice. Managerial Summary:Our analysis shows that although biases by themselves are unequivocally harmful for firms, both the entrant and incumbent can earn more when they are biased than when neither one is. In particular, when an entrant is biased in estimating an incumbent's repositioning ability, this unequivocally reduces its own performance, if the incumbent is aware of the entrant's bias and has correctly assessed it. In a similar vein, when an incumbent is biased in its estimation of the entrant, this hurts the incumbent. However, both the entrant and the incumbent can earn more than they would in a setting where both firms are unbiased. Furthermore, the incumbent is not necessarily better off by being less biased—that is, aware of but with an inaccurate assessment of entrant bias.]